Biopharmaceuticals at the Frontier of Medical Therapeutics: Monoclonal antibodies, RNAs and Gene editing - Galindo Sevilla, Norma del Carmen; Mancilla Galindo, Javier (Horizonte Sanitario, 2025)
In recent years, new medical treatments have been developed using biological molecules that are part of the defense mechanisms of living organisms. These molecules target specific components involved in disease processes, such as those associated with cancer. One example of such strategies are monoclonal antibodies, immune system molecules designed to neutralize specific targets. The in vitro production of these humanized antibodies has permitted homogeneity, industrial-scale production, and similarity to human proteins, which prevents their rapid degradation. These treatments are currently successfully applied to various diseases, including cancer, hypersensitivity, autoimmune, degenerative, and metabolic disorders. Another class of emerging therapeutic molecules are ribonucleic acids (RNA) in their various forms, such as aptamers, antisense oligonucleotides (ASOs), messenger RNAs (mRNAs), small interfering RNAs (siRNAs), and microRNAs (miRNAs). The market entry of these therapies has been so rapid that, to date, approximately 700 RNA products have been approved for human use in the United States, compared to the 125 authorized humanized monoclonal antibodies. While antibodies and RNA products are administered periodically, gene editing is being researched with the aim of correcting mutated genes that cause disease. Although this field has made significant advancements, it poses the greatest ethical dilemmas and challenges. Keywords: Biological Products; Monoclonal antibody; RNAi Therapeutics; Genetic Therapy; Gene Editing.